2019
DOI: 10.1108/imr-02-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

Architectural marketing capabilities of exporting ventures

Abstract: Purpose -The importance of architectural marketing capabilities (i.e., marketing planning and implementation) in exporting ventures has been recognised. However, extant literature has not taken into account the explicit roles and required synergy between the exporter and their foreign distributor in delivering these capabilities. Drawing from the Resource Based Theory, we examine the complementarity of the distributor's implementation capabilities and market orientation with the exporter's planning capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…2.2.3 Architectural marketing capability. The development of advanced-level procedures to create and carry out strategic decisions that are vital for the accomplishment of SMEs' strategic marketing modification goals and performance improvement is what AMC entails (Theoharakis et al, 2019). Thus, the core of SMEs' AMC is the strategic marketing planning process and related execution processes.…”
Section: Marketing Modificationmentioning
confidence: 99%
“…2.2.3 Architectural marketing capability. The development of advanced-level procedures to create and carry out strategic decisions that are vital for the accomplishment of SMEs' strategic marketing modification goals and performance improvement is what AMC entails (Theoharakis et al, 2019). Thus, the core of SMEs' AMC is the strategic marketing planning process and related execution processes.…”
Section: Marketing Modificationmentioning
confidence: 99%
“…Most of the studies were performed in Europe, mainly in EU-15 countries (Spain, Greece, Portugal, Sweden, Netherlands, Italy, Austria, Germany) and UK ( To analyze the most significant capabilities as export performance determinants, authors categorized them and synthesized how often the factor was used in studies and what kind of effect was found on export performancepositive, negative, no effect of other type of effect (Table 2). Source: author's synthesis based on D 'Angelo et al, 2013;Assadinia et al, 2019;Azar and Ciabuschi, 2017;Bloemer et al, 2013;Boso et al, 2013;Boso et al, 2019;Cadogan et al, 2012;Chung et al, 2019;Di Fatta et al, 2019;Eid et al, 2019;Ferreras-Méndez et al, 2019;Gregory et al, 2019;Haddoud et al, 2019;Hofer et al, 2019;Hughes et al, 2010;Kaleka, 2012;Katsikea et al, 2019;Krammer et al, 2018;Kuivalainen et al, 2013;Monteiro et al, 2019;Mostafiz et al, 2019;Oura et al, 2015;Pham et al, 2017;Pyper et al , 2019;Ramon-Jeronimo et al, 2019;Rua, 2018;Silva et al, 2017;Sousa et al, 2010;Theoharakis et al, 2019;Wang et al, 2013;Zhao et al, 2018 The results (Table 2) show that most frequent capability factors used in research models are marketing, innovation and networking capabilities. Although these factors have proved to have mostly positive effect on performance, marketing capabilities show the largest frequency of results with no effect or negative effect on export performance.…”
Section: Summary Of Empirical Studies Of Capabilitiesmentioning
confidence: 99%
“…Significantly, along with firm' s own marketing capabilities, we notice the role of distributors' capabilities. Theoharakis et al, 2019 propose that it is not enough to analyze only exporting firm's capabilities and researchers should include also distributors capabilities. In their study authors found that the effect of exporters own marketing planning capabilities was smaller if distributors marketing capabilities were low.…”
Section: Marketing Capabilities As Export Performance Determinantsmentioning
confidence: 99%
“…The authors highlight that MNCs show commitment to CSR programs, although underdeveloped and weak formal institutions, and that lots of these activities are focused toward norms-based social CSR marketing. With regard to a developed country, through interviews with nine export ventures that originated from Greece, Theoharakis et al (2019) highlight the relevance of exporter planning capability on financial performance (overall profit, profit margins, return on investment and return on sales) and the complementary role of distributor market orientation. Further, the authors find that the distributor's implementation capability partially mediates the impact of the exporter's planning capability on financial performance.…”
Section: Thematic Analysis Of the Literaturementioning
confidence: 99%